2013
DOI: 10.1080/13557858.2012.698254
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering acculturation in dietary change research among Latino immigrants: challenging the preconditions of US migration

Abstract: BACKGROUND Dietary changes among Latino immigrants are often attributed to acculturation. Acculturation-diet research typically assumes that migration to the US is necessary for negative dietary changes to occur in Latino immigrants’ diets. OBJECTIVE The goal of this article is to demonstrate that extant acculturation research is not adequate in capturing changes in Latino immigrants’ diets. This is due to the role of globalization and transnational processes in modernizing their diets in Latin America. DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Further, the larger study afforded measures of a broad range of factors related to diabetes, and in turn their inclusion and the analytic models construction were guided by social ecological theory. This data also well compliments other efforts to understand Hispanic health such as an intensive ongoing study in four major urban environments [52]. It is important to note that the response rate was outstanding, particularly for a study without monetary incentives.…”
Section: Discussionsupporting
confidence: 78%
“…Further, the larger study afforded measures of a broad range of factors related to diabetes, and in turn their inclusion and the analytic models construction were guided by social ecological theory. This data also well compliments other efforts to understand Hispanic health such as an intensive ongoing study in four major urban environments [52]. It is important to note that the response rate was outstanding, particularly for a study without monetary incentives.…”
Section: Discussionsupporting
confidence: 78%
“…Of particular relevance to the current study, recent qualitative data from Latino immigrants in California (27 in‐depth interviews) demonstrate that globalization‐facilitated negative dietary changes begin in urban Latin America as a precondition to migration (Martínez, ). Based on this finding, Martinez issued a call to examine dietary changes through globalization and transnational lenses rather than through a traditional immigrant acculturation lens.…”
Section: Remote Acculturationmentioning
confidence: 97%
“…A study in New York City found that Latinas living in neighborhoods with a greater percentage of Spanish-speaking households had higher diet quality (Park et al, 2011). Overall, literature on acculturation and diet in Latinos suggests an association between acculturation to the U.S. diet and poor diet quality, with the caveat that such associations are often cross-sectional in nature and fail to incorporate a transnational perspective (Martínez, 2013;P erez-Escamilla and Putnik, 2007). Because higher BMI and poor diet, two important risk factors for gestational diabetes, are associated with increased time in the U.S., and living outside of a residential ethnic enclave is associated with increased time in the U.S., it is plausible that living in a residential ethnic enclave is associated with a reduced risk of gestational diabetes.…”
Section: Introductionmentioning
confidence: 94%